Association of systolic blood pressure with cardiovascular outcomes in elderly patients with hypertension in Northern China. Issue 5 (October 2018) - Guo, Xiaobin; Liu, Yesong; Yang, Nan; Liu, Ping; Zhu, Ying; Xia, Xiaoshuang; Yu, Wenxia; Zhao, Chumin; Wang, Lin; Wu, Shouling; Li, Xin
Abstract : Objective: The aim of this study was to investigate the association of systolic blood pressure (SBP) with cardiovascular disease and all-cause mortality among elderly hypertensive patients in northern China. Participants and methods: In this prospective cohort study, 9655 elderly hypertensive patients from Kailuan study were followed up with the incidence of primary outcomes (composite outcomes including myocardial infarction, stroke, and all-cause death) and the incidence of secondary outcomes (stroke, myocardial infarction, and all-cause death). Patients were categorized into five groups on the basis of SBP levels: Q1 (SBP<130 mmHg), Q2 (130⩽SBP<140 mmHg), Q3 (140⩽SBP<150 mmHg), Q4 (150⩽SBP<160 mmHg), and Q5 (SBP≥160 mmHg). Results: During an average of 7.2±1.6 years of follow-up, patients in the group Q2 had the lowest incidence rates of composite outcomes. Q1 was not associated with a decreased risk of composite outcomes. Interestingly, compared with reference group Q2, the risk of composite outcomes [hazard ratio (HR): 1.36; 95% confidence interval (CI): 1.06–1.75] was significantly increased in the Q3 subgroup with high risk+very high risk for the incidence of ischemic cardiovascular disease (ICVD). Similarly, the risk of composite outcomes (HR: 1.25; 95% CI: 1.01–1.53 and HR: 1.35; 95% CI: 1.04–1.75) was significantly increased in Q4 subgroups, with both intermediate risk and high risk+very high risk for 10-year ICVD. Conclusion: Elderly hypertensive patients with a high risk of 10-year ICVD were still at a higher risk of developing adverse outcomes even with 140⩽SBP<150 mmHg. SBP of less than 130 mmHg was not associated significantly with a reduced risk of developing adverse outcomes.